Ineficiências e iniquidades do imposto de renda: Da agenda negligenciada para a próxima etapa da reforma tributária - Sérgio Wulff Gobetti (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– This study contributes to the debate on income taxation reform by presenting a broad and detailed diagnosis of the various distortions of the current model. In particular, it shows how the inequities perpetuated in both the IRPF and IRPJ legislation generate economic inefficiency, in addition to weakening the principle of progressivity. A wide range of adjustment measures, based on both international trends and Brazilian particularities, are presented as alternatives for a structural reform of the system.
Keywords: H2; H3; 330; taxation; progressivity; equity and efficiency